Investigation of reactive multiphase characteristics in a chemical looping combustion process of biomass with hematite as oxygen carrier. (15th October 2021) - Dong, Ruihan; Yang, Shiliang; Hu, Jianhang; Chen, Fangjun; Wang, Hua
Graphical abstract: Highlights: Multiphase reactive flow in fuel reactor of chemical looping combustion is explored. Oxygen carrier has a larger heat transfer coefficient as compared with biomass. HTC of both particle species negatively correlates to the solid concentration. A positive correlation between HTC and Reynolds number is observed. Different axial temperature distribution is observed for oxygen carrier and biomass. Abstract: Chemical looping combustion is a new combustion technology to reduce the costs and energy penalty for the capture of carbon dioxide. In this work, a three-dimensional fuel reactor model with hematite as oxygen carrier is established by computational fluid dynamics coupled with the multiphase particle-in-cell method. After model validation, the thermochemical properties of gas and solid phases in the fuel reactor are explored, including the components, slip velocity, Reynolds number and temperature. The results show that the asymmetric distribution of combustible gas concentrations is attributed to biomass injection. The oxygen carrier particles have a larger heat transfer coefficient than the biomass particles. The heat transfer coefficient of both particle species negatively correlates to the solid concentration, but positively correlates to the slip velocity and Reynolds number. The biomass particles behave with a wide range and higher value of the Reynolds number. Different axial variations of the temperature can be observed for the oxygen carrier and biomass. Moreover, a nearly 50 K temperature difference exists between the biomass and oxygen carrier. Reducing the oxygen carrier size and enlarging the superficial velocity increase the heat transfer coefficient and temperature of both particle species.